2021
DOI: 10.1142/s0218202521500408
|View full text |Cite
|
Sign up to set email alerts
|

What is life? A perspective of the mathematical kinetic theory of active particles

Abstract: The modeling of living systems composed of many interacting entities is treated in this paper with the aim of describing their collective behaviors. The mathematical approach is developed within the general framework of the kinetic theory of active particles. The presentation is in three parts. First, we derive the mathematical tools, subsequently, we show how the method can be applied to a number of case studies related to well defined living systems, and finally, we look ahead to research perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 113 publications
1
24
0
Order By: Relevance
“…A study about childhood vaccinations suggested pro-vaccine parents can influence those who may be vaccine hesitant [ 41 ]. Thus, guiding people through the social influence of leaders (e.g., trained personnel or peer/personal opinion leaders) can greatly facilitate crowd management during emergencies [ 47 ], similar to how pro-vaccine parents can help correct vaccine misinformation in-person or online [ 41 , 42 , 47 ]. Such messenger-led and peer-endorsed health communication interventions are simple and efficient in design, can give voice to the science for all stages from vaccine development to vaccination, and have the desired impact on the larger population.…”
Section: Discussionmentioning
confidence: 99%
“…A study about childhood vaccinations suggested pro-vaccine parents can influence those who may be vaccine hesitant [ 41 ]. Thus, guiding people through the social influence of leaders (e.g., trained personnel or peer/personal opinion leaders) can greatly facilitate crowd management during emergencies [ 47 ], similar to how pro-vaccine parents can help correct vaccine misinformation in-person or online [ 41 , 42 , 47 ]. Such messenger-led and peer-endorsed health communication interventions are simple and efficient in design, can give voice to the science for all stages from vaccine development to vaccination, and have the desired impact on the larger population.…”
Section: Discussionmentioning
confidence: 99%
“…The output accounts for the heterogeneity of the immune defence within a susceptible population and predicts the different outputs of the dynamics, namely full recovery, need of hospitalization and death. The mathematical framework is that of the mathematical theory of active particles [16], for systems which operate far from equilibrium. This approach has been used also in different types of scientific investigations, for instance modelling contagion dynamics in crowds, from the pioneering article [17] to more recent developments [18,19], transport of compartmental models in the territory [20], or models accounting for social distance [21].…”
Section: Aims and Plan Of The Articlementioning
confidence: 99%
“…The model focuses on the dynamics of vaccination which has shown to be the most effective action developed to tackle the pandemic. The contents are presented in the following three subsections, where firstly, we derive a multiscale model of the aforementioned dynamics based on a development of the mathematical theory of active particles [16]. The model refers to a population with homogeneous ability of the immune defence.…”
Section: Modelling Vaccinationmentioning
confidence: 99%
“…According to the research scale, dynamic crowd models can be divided into three types: microscale models, [10][11][12][13][14][15][16] macroscale models, [17][18][19][20][21][22][23] and mesoscale models (kinetic models). [24][25][26][27][28][29][30][31][32] Microscale models are used to analyze and model individual motion characteristics and they include the social force model and the cellular automaton model. The social force model originated from Lewin's domain theory 10 and was developed based on Helbing's introduction of Newton's mechanical concept.…”
Section: Introductionmentioning
confidence: 99%